Strategi Berpikir Kreatif untuk Meningkatkan Kemampuan Membaca Pemahaman Siswa Kelas V Sekolah Dasar - Mutia Dwi Andini; Chandra Chandra; Salmaini Safitri Syam (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study explores creative thinking strategies aimed at enhancing reading comprehension skills among fifth-grade elementary school students. By focusing on developing critical and innovative thinking methods, the research investigates how these strategies can improve students' ability to understand and process reading materials. The study employs various approaches to stimulate cognitive engagement, fostering both deeper comprehension and greater interest in reading. Results suggest that incorporating creative thinking techniques significantly contributes to the enhancement of students' reading comprehension abilities. The findings highlight the importance of integrating these strategies into the classroom to support students' academic growth and encourage lifelong learning habits.